Investigating the biomechanical properties of fresh goat skin, natural dried skin and leather / Siti Hajar Mohd Yusop - Mohd Yusop, Siti Hajar (2015)
Natural dried skin and leather which comes from fresh skin has been used for many applications in the automotive sector, furniture, clothes and other industries. However, the biomechanical properties of these materials have not been well established. Therefore, this study attempts to quantify and investigate the parameters o f fresh goat skin (Category I), natural dried skin (Category II) and leather (Category III), which also include orthotropic analysis (longitudinal and transverse directions). Uniaxial tensile test (ASTM D2099-00) was conducted to obtain engineering stress-stretch data for all categories. Analytical and numerical approaches were also adapted to quantify the material parameters. Engineering stress-stretch curves for both approaches were fitted to the experiment data by adapting three hyperelastic materials models (i.e. neo-Hookean, Mooney-Rivlin and Ogden). Numerical approach adapting the Ogden model is likely the best hyperelastic material model in representing the parameters o f fresh goat skin, natural dried skin and leather. For each category, the Ogden parameters (a and |j.) range value were found from 15.154 to 18.344 and from 0.152 MPa to 0.277 MPa (Category I), from 0.675 to 5.652 and from 107.416 MPa to 1185.859 MPa (Category II) from 14.815 to 15.885 and from 1.827 MPa to 4.441 MPa (Category III)respectively. This study also found out that among fresh goat skin, natural dried skin and leather, natural dried skin was the stiffest skin of them all. As a conclusion, the biomechanical properties of fresh goat skin, natural dried skin and leather has been quantified, and thus proving that the objective o f the study has been achieved successfully.